Pengaruh Promosi Flash Sale Terhadap Minat Beli pada E-Commerce Shopee - Supriyatna, Nana; Yatna (Ikatan Da'i Indonesia, 2025)
The rapid advancement of technology has encouraged the emergence of e-commerce which makes it easier to make transactions online, but with that the competition in the business world is getting tighter, this requires business people to innovate and create creative and attractive marketing strategies, one of which is flash sale promotions. This study aims to determine whether flash sale promotions have an influence or not on buying interest in shopee e-commerce. This study applies a quantitative model with a causal approach. The population of this study were shopee application users. The sample was taken using nonprobability sampling technique with incidental sampling, obtained data as many as 100 respondents. The data analysis technique uses validity test, reliability test, classical assumption test, simple regression model, coefficient of determination (R2). Hypothesis tested with partial test (t test). The results of this study are that the flash sale promotion variable affects buying interest positively and partially significant with the equation Y = 10.257 + 0.761X1, and the coefficient of determination of 54.5% on buying interest in buying interest and the remaining 45.5% is affected by other elements.